Murder season - Ellis, Robert, 1954- (Minotaur Books, 2011)
"Detective Lena Gamble knows how to handle the hottest cases--do it fast and keep her head down because if it all goes south, the department won't hesitate to make a scapegoat out of her. So when she gets called to the scene of a double murder at Club 3 AM, the A-list hangout for Hollywood celebs, she knows the fun is only beginning. And she's not wrong. It's just much worse than that. As expected, one of the victims is club owner Johnny Bosco, one of the most well-connected men in Hollywood politics. But the shocker comes when Lena sees the other: 25-year-old Jacob Gant, acquitted just days ago of murdering his 16-year-old neighbor, after L.A.'s latest trial-of-the-century. But are these victims of a father's righteous anger or is something bigger at play? Robert Ellis's third white-knuckled thriller delivers all the twists and turns fans have come to expect, with plenty more to spare"--